頸髄損傷者の運動時深部温上昇を抑制するためのアイススラリー摂取の可能性を探索する予備的研究 - 中村 知寛; 小出 夏希; 加藤 彩菜; 上田 ほのか; 谷口 佑香; 後藤 早希; 窪 優太; 林 浩之 (作業療法, 2024)
要旨：【目的】本研究は頸髄損傷完全麻痺者を対象とし，運動前にアイススラリーを摂取することが運動中の深部温上昇抑制に作用するか検証した．【方法】本研究はシングルケーススタディBCB'デザインを用い，対象者は4名であった．対象者は各期での運動開始前に冷却飲料水またはアイススラリーを摂取し，運動として10分間車いすを駆動した．運動開始直後および毎分に鼓膜温を測定した．各期で得られた深部温については勾配を算出し，各期での変化を判定した．【結果】対象者2名は，アイススラリー摂取期に冷却飲料水よりも深部温上昇を抑制できた．【結論】運動前にアイススラリーを摂取することで運動中の深部温上昇を抑制できる可能性がある. 　This study investigated whether ingestion of ice slurry before exercise suppresses core temperature elevation in subjects with cervical spinal cord injury. This study used a single case study BCB' design and included four subjects. The subjects consumed cooled drinking water or ice slurry before the start of exercise in each period and propelled a wheelchair for 10 minutes as exercise. Core temperature was measured by tympanic temperature immediately after the start of exercise and every minute. The tympanic temperatures obtained in each period were used to calculate the slope and determine the change in each period. The two subjects showed less increase in tympanic temperature during the ice slurry intake period than during the cooled drinking water intake period. Consumption of ice slurry before exercise may reduce the increase in core temperature during exercise.